دراسة تحليلية لتداعيات الجائحة على صعيد الاقتصاد و سوق العمل حالة الاقتصادات المتقدمة و البلدان النامية - بلغنامي, نجاة وسيلة (جامعة الوادي - University of Eloued, 2023)
In the wake of the spread of the new mutated Omicron strain of the Corona virus and in the context of the current crisis, a study came to analyze the effects of the pandemic on the global economy and the labor market, where several governments have been managing recovery paths to get out of this health and economic crisis on him. We try through this study to highlight the most important The expectations stated in the report, which are represented in: The medium-term losses are expected to be less than the losses that followed the global financial crisis, with a decrease of about 3% from the expected global output before the outbreak of the pandemic recovery of the global economy, with growth reaching 6% in a year 2021 and 4.4% in 2022.Due to the varying speed of response and the possibility of economic damage between countries. High global unemployment rate of 5.7%. It projected 205 million people in 2022, far exceeding the level of 187 million people recorded in 2019
Analytical study of the repercussions of the pandemic at the level of the economy and the labor market The state of advanced economies and developing countries
مقال
Keywords: النمو الاقتصادي ; الجائحة و الازمة ; سوق العمل ; البطالة ; سوق مالي